SAORAJA SAWITTO SEBAGAI SUMBER PEMBELAJARAN UNTUK MEMBANGUN KESADARAN SEJARAH - Bahri Bahri; Achmad Idrus Al Islami; Najamuddin Najamuddin (Humano: Jurnal Penelitian, 2023)
The position of history education in schools is less desirable, especially for students because history is synonymous with knowing and memorizing historical events or facts, and the teacher's lack of maximum use of learning resources in the surrounding environment will lead to boredom for students. Teaching history by emphasizing the use of historical sites around students is a solution so that learning history can be more easily understood. This study aims to determine the history of Saoraja Sawitto Kingdom, the use of the local site of the Saoraja Sawitto Traditional House as a source of learning history, the supporting and inhibiting factors of the local site of the Saoraja Sawitto Traditional House as a source of learning history. The research method used is the historical method with 4 steps, namely Heuristics, Criticism, Interpretation, and Historiography. Based on the research conducted, it was found that the Saoraja Sawitto traditional house was the home of the Kedatuan Sawitto Royal Palace which was formerly made of wood, but during the Colonial reign there was a change in the structure of the building which then changed its shape to a stone house. With the local historical site of Saoraja Sawitto, students are active and enjoy learning so that it can facilitate the teaching and learning process, especially in history subjects. One of the factors supporting the use of this existing house, namely the enthusiasm of students, and one of the inhibiting factors is the lack of literature regarding the Saoraja Sawitto traditional house.